Enhanced Recovery After Surgery (ERAS®) in thoracic surgical oncology. (March 2018) - Gonfiotti, Alessandro; Viggiano, Domenico; Bongiolatti, Stefano; Bertolaccini, Luca; Solli, Piergiorgio; Bertani, Alessandro; Voltolini, Luca; Crisci, Roberto; Droghetti, Andrea
Enhanced recovery after surgery (ERAS ® ) is a strategy that seeks to reduce patients' perioperative stress response, thereby reducing potential complications, decreasing hospital length of stay and enabling patients to return more quickly to their baseline functional status. The concept was introduced in the late 1990s and was first adopted for use with patients undergoing open colorectal surgery. Since that time, the concept of ERAS has spread to multiple surgical specialties. This article explores the key elements for patient care using an ERAS protocol applied to minimally invasive thoracic surgery.